2016
DOI: 10.17305/bjbms.2016.853
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab inhibits neuronal cell apoptosis and activates STAT3 in cerebral infarction rat model

Abstract: Cerebral infarction is a severe hypoxic ischemic necrosis with accelerated neuronal cell apoptosis in the brain. As a monoclonal antibody against interleukin 6, tocilizumab (TCZ) is widely used in immune diseases, whose function in cerebral infarction has not been studied. This study aims to reveal the role of TCZ in regulating neuronal cell apoptosis in cerebral infarction. The cerebral infarction rat model was constructed by middle cerebral artery occlusion and treated with TCZ. Cell apoptosis in hippocampus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…In addition, tocilizumab treatment rescued the loss of Safranin O staining, which reflects glycosaminoglycan content in the articular cartilage matrix 30 . Consistent with these findings, tocilizumab treatment has been shown to reduce neural cell apoptosis in a rat model of cerebral infarction and in oxygen-glucose deprived culture conditions 31 . Similarly, tocilizumab treatment significantly inhibited apoptosis and increased proliferation viability of human cardiac myocytes in culture conditions simulating ischemic reperfusion injury 32 .…”
Section: An Anabolic Effect Of Tocilizumab On the Cartilage Matrix Wimentioning
confidence: 57%
“…In addition, tocilizumab treatment rescued the loss of Safranin O staining, which reflects glycosaminoglycan content in the articular cartilage matrix 30 . Consistent with these findings, tocilizumab treatment has been shown to reduce neural cell apoptosis in a rat model of cerebral infarction and in oxygen-glucose deprived culture conditions 31 . Similarly, tocilizumab treatment significantly inhibited apoptosis and increased proliferation viability of human cardiac myocytes in culture conditions simulating ischemic reperfusion injury 32 .…”
Section: An Anabolic Effect Of Tocilizumab On the Cartilage Matrix Wimentioning
confidence: 57%
“…Certain diseases or genetic factors can change the characteristics of the cerebral vascular systems and contribute to cerebral infarction or other CSVDs. [ 18 , 42 ] In the blood vessel development, the Notch signaling pathway regulates the expression of many genes involved in the cell proliferation, differentiation, apoptosis, and cell fate decision, [ 26 ] and coordinates arterial differentiation of endothelial cells. [ 43 – 46 ] Targeted mutations of the Notch target genes could result in embryonic lethality due to severe defects in the angiogenic vascular remodeling.…”
Section: Discussionmentioning
confidence: 99%
“…The risk factors so far documented include smoking, obesity, dyslipidemia, high blood pressure, diabetes and aging, [ 14 , 15 ] and the pathogenesis involves neuronal cell apoptosis. [ 16 , 17 ] Blockage of the brain blood vessels is the direct cause of the disease, resulting from embolism or thrombosis and leading to cerebral ischemia, [ 18 ] which may induce immune responses and inflammation. [ 15 , 19 23 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, we have to remain cautious and more data are necessary on the impact of TNF-α inhibitors on IS as it has been observed that TNF-α inhibition was associated with increased ischemic damage following a decrease in innate immune response from the brain ( Pires et al, 2014 ). Considering IL6, it has been reported that pre-treatment with tocilizumab, a monoclonal antibody against IL6 in a rat model of ischemic stroke, prevents neuronal cell apoptosis ( Wang et al, 2016 ).…”
Section: Neuroinflammationmentioning
confidence: 99%